Social Impact Assessment Models - Raluca ANTONIE (GÂRBOAN) (Transylvanian Review of Administrative Sciences, 2010)
The aim of impact assessment in the public  domain is to estimate accurately the largest  possible extent to which interventions or actions  achieve their objectives. Such estimates are,  inevitably, to a certain degree plausible. But as  the model used is more rigorous, the results will  be more accurate. But what is a rigorous model for  social impact assessment? And, most importantly,  what model would be appropriate to estimate the  social impact for the public sector in Romania? This  paper is meant to analyze the main trend of models  for social impact assessment in public sphere in  general and in Romanian public administration  in particular.